2010
DOI: 10.1016/j.ijimpeng.2010.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Perforation of sandwich plates with graded hollow sphere cores under impact loading

Abstract: In this paper, sandwich plates made from 0.8mm 2024 T3 aluminium alloy skin sheets and graded polymeric hollow sphere cores (having various density gradients) are studied. The experiments at 45m/s were performed with an inversed perforation setup using SHPB system. Quasi-static tests using the same clamping system allow for the rate effect investigation. Numerical simulations are performed in order to get the indispensable local information (which is not experimentally available) to better understand the perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
27
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 14 publications
2
27
0
Order By: Relevance
“…One important result from their work suggested placing the high density foam core against the top surface skin for an improved perforation resistance. Zeng and coauthors [17] developed sandwich plates with face sheets made of aluminum alloy while the cores were made of graded polymeric hollow sphere composite with various density gradients. The authors concluded that the best gradient profile in terms of the energy absorption and the non-sheet breaking criterion should be a weaker first layer and a progressively enhanced core.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One important result from their work suggested placing the high density foam core against the top surface skin for an improved perforation resistance. Zeng and coauthors [17] developed sandwich plates with face sheets made of aluminum alloy while the cores were made of graded polymeric hollow sphere composite with various density gradients. The authors concluded that the best gradient profile in terms of the energy absorption and the non-sheet breaking criterion should be a weaker first layer and a progressively enhanced core.…”
Section: Introductionmentioning
confidence: 99%
“…17 shows the thermal gradient versus diameter difference between T L and T H sides for 10% microspheres loading and different T L values. The trend of increasing diameter difference with increasing thermal gradient was observed at T L of 160 C for all T H values.…”
mentioning
confidence: 99%
“…Because of the outstanding properties, such as the low weight and high efficient energy absorption [1,2], the metallic cellular materials have been extensively applied in the civilian and aerospace fields (e.g., reentry capsule and airdrop platform) for impact mitigation applications. Among the metallic cellular materials, the gradient metallic cellular material has attracted many research interests [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The relatively stiffer outer part of smaller cell size provides higher resistance to external loads such as bending and buckling while the less dense inner part of larger cell size reduces its total weight. Recently, a few studies on graded cellular solids have been carried out, showing that they may have some merits when employed appropriately [20][21][22][23][24][25][26]. However, the underlying mechanism of high velocity crushing remains not reasonably understood.…”
Section: Introductionmentioning
confidence: 99%